GAP ANALYSIS OF SMART MOBILITY IMPLEMENTATION AROUND THE MANDALIKA AREA - Aprianto, Rizal; Reza Yoga Anindhita; Ramadhan Dwi Prasetyo (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2024)
The presence of the Mandalika Tourism Area has become one of the driving factors for the selection of Mataram City, North Lombok Regency, East Lombok Regency, West Lombok Regency, and Central Lombok Regency as cities/regencies participating in the "100 Smart City Movement" program. The arrival of tourists in the circuit needs to be seen as a potential for the surrounding areas to accelerate development in various sectors, including transportation. This research is conducted to analyze the readiness of implementing smart mobility in the 5 areas around the Mandalika Tourism Area as one aspect in realizing a smart city, as well as the challenges faced in implementing smart mobility. In this study, a deductive approach through literature surveys and questionnaire distribution, as well as a qualitative descriptive approach through Forum Group Discussion (FGD) with related government agencies (OPD), are used. The Customer Satisfaction Index (CSI) method is used to obtain parameters for public satisfaction with public transportation services. From the analysis results, all areas are still classified as conditionally ready, but there are still several aspects of smart mobility that need to be fulfilled and improved.